2021
DOI: 10.1002/nau.24597
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of urinary incontinence among Iranian women

Abstract: Background: Urinary incontinence is a common condition among women. Although it is not a life-threatening condition, it dramatically influences the quality of life. This study aimed to estimate the prevalence of urinary incontinence and its risk factors among Iranian women in Kerman, Iran. Methods: This cross-sectional, population-based study was conducted on 3100 Iranian women aged 15-80 years in 2017 in Kerman, Iran. The participants were selected via cluster sampling and were invited to complete the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The sixth item is related to the time and type of urine leakage (not considered). The total score ranges from 0 to 21; mild (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and very severe (19)(20)(21). A higher score indicates the intensity of UI.…”
Section: International Consultation On Incontinence Questionnaire-uri...mentioning
confidence: 99%
See 1 more Smart Citation
“…The sixth item is related to the time and type of urine leakage (not considered). The total score ranges from 0 to 21; mild (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and very severe (19)(20)(21). A higher score indicates the intensity of UI.…”
Section: International Consultation On Incontinence Questionnaire-uri...mentioning
confidence: 99%
“…Due to the limited research on the Iranian population [ 16 , 17 ], the increase in mean life expectancy, and the prevalence of urinary incontinence and its impact on various aspects of life, our study aimed to determine the prevalence and severity of urinary incontinence and its related factors in a health centers-based sample of postmenopausal women in Tabriz-Iran. Caregivers better provide appropriate treatments to reduce the prevalence of UI through educating, preventing, and reducing the impact of risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of UI increases with advancing age. Studies from several countries have shown that the prevalence of UI ranges from 21.4% to 63% 13–21 . In Turkey, the prevalence of UI varies between 17.5% and 88.1% 8,9,12,22–25 …”
Section: Introductionmentioning
confidence: 99%
“…Stress urinary incontinence (SUI), referring to the involuntary leakage of urine in the presence of an increase in intra-abdominal pressure, is a prevalent condition among women. It occurs as a result of urethral sphincter deficiency or pelvic floor muscle and fascial supporting tissue weakness [1][2][3] . Initial treatments for urinary incontinence are conservative treatments, including pelvic floor physiotherapy, biofeedback, electrical stimulation, and in some cases, pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%